2021
DOI: 10.1159/000517910
|View full text |Cite
|
Sign up to set email alerts
|

Objective Thoracoscopic Criteria in Differentiation between Benign and Malignant Pleural Effusions

Abstract: <b><i>Background:</i></b> Thoracoscopy is the “gold standard” diagnostic modality for investigation of suspected pleural malignancy. It is postulated that meticulous assessment of the pleural cavity may be adequate to indicate malignancy through the macroscopic findings of nodules, pleural thickening, and lymphangitis. We attempted to critically assess this practice, by precisely defining objective macroscopic criteria which might differentiate benign from malignant pleural diseases acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, while nodules were the predominant pattern in malignant pleural disease, they were also detected in 24% of benign etiologies [80]. In a study of 100 consecutive pleural biopsies with benign diagnosis (no cancer), the predominant macroscopic pattern was inflammatory in 40% of cases, fibrinous in 14%, septated in 8%, fibrous in 6%, hemorrhagic in 2%, and pleural plaques in 2% [72].…”
Section: Non-specific Pleuritismentioning
confidence: 99%
See 1 more Smart Citation
“…However, while nodules were the predominant pattern in malignant pleural disease, they were also detected in 24% of benign etiologies [80]. In a study of 100 consecutive pleural biopsies with benign diagnosis (no cancer), the predominant macroscopic pattern was inflammatory in 40% of cases, fibrinous in 14%, septated in 8%, fibrous in 6%, hemorrhagic in 2%, and pleural plaques in 2% [72].…”
Section: Non-specific Pleuritismentioning
confidence: 99%
“…The first possibility is associated to the frequently complicated macroscopic appearance of the pleural cavity making it difficult to select the biopsy sites. A recent study describing the macroscopic features of the pleura during thoracoscopy showed that pleural disease of benign etiology presented principally an inflammatory macroscopic aspect with the most affected areas being the middle and inferior lateral costoparietal pleura, while in the malignant group, nodules were the predominant finding actually affecting the same localization [80].…”
Section: Non-specific Pleuritismentioning
confidence: 99%
“…Furthermore, Carlo Forlanini, in Pavia, Italy, used a similar method in 1882 to create an artificial pneumothorax and induce lung collapse, a treatment that was thought to be beneficial in pulmonary tuberculosis [ 2 ]. Direct visualisation of the pleura enables biopsies to be taken from the parietal pleura and pleural-based abnormalities such as nodules, increasing diagnostic yield, particularly in malignancy [ 3 ]. At the same time, any fluid can be drained offering symptomatic relief to the patient and measures such as talc pleurodesis or indwelling drains can be respectively performed or inserted for fluid management [ 4 ].…”
Section: Introductionmentioning
confidence: 99%